2005
DOI: 10.1080/10635150590910249
|View full text |Cite
|
Sign up to set email alerts
|

Is Homoplasy or Lineage Sorting the Source of Incongruent mtDNA and Nuclear Gene Trees in the Stiff-Tailed Ducks (Nomonyx-Oxyura)?

Abstract: We evaluated the potential effects of homoplasy, ancestral polymorphism, and hybridization as obstacles to resolving phylogenetic relationships within Nomonyx-Oxyura stiff-tailed ducks (Oxyurinae; subtribe Oxyurina). Mitochondrial DNA (mtDNA) control region sequences from 94 individuals supported monophyly of mtDNA haplotypes for each of the six species and provided no evidence of extant incomplete lineage sorting or inter-specific hybridization. The ruddy ducks (O. j. jamaicensis,O. j. andina, O. j. ferrugine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 45 publications
8
107
0
1
Order By: Relevance
“…Our results are consistent with the hypothesis suggested by several authors (Fjeldså, 1986; McCracken & Sorenson, 2005; Siegfried, 1976) that the Colombian population of Ruddy Ducks might be of hybrid origin. Variation in all genes indicated that the Colombian population shares alleles with populations from both North America and the Southern Andes as expected for an admixed population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with the hypothesis suggested by several authors (Fjeldså, 1986; McCracken & Sorenson, 2005; Siegfried, 1976) that the Colombian population of Ruddy Ducks might be of hybrid origin. Variation in all genes indicated that the Colombian population shares alleles with populations from both North America and the Southern Andes as expected for an admixed population.…”
Section: Discussionsupporting
confidence: 93%
“…Our sampling scheme also allowed us to address the question of whether the Colombian population of Ruddy Ducks may be of hybrid origin as suggested by its wide variation in male facial plumage (Fjeldså, 1986; McCracken & Sorenson, 2005; Siegfried, 1976). Our extended sampling suggests that there is likely more complexity to biogeographic and evolutionary scenarios proposed by earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…the real species phylogeny (Tajima, 1983). The conflicts between gene trees and species trees could be caused by incomplete lineage sorting, hybridization, gene duplication or branch length heterogeneity (Edwards, 2009;McCracken and Sorenson, 2005;McGuire et al, 2007). Therefore, results from species-level phylogenies that have used only a single locus or a concatenated gene matrix should be interpreted cautiously (Wahlberg et al, 2009).…”
Section: Gene-tree and Species-tree Conflicts On Phylogenetic Inferencementioning
confidence: 99%
“…In the case of relationships involving short branches, theoretical models indicate that when the time of shared ancestry is short compared to that of independent ancestry (e.g., short internodal branches leading to long terminal branches), the number of informative characters will be so small that the probabilities of recovering a bifurcating pattern is low (Lanyon, 1988). Moreover, signals of common ancestry (i.e., synapomorphies) are most likely to be overwritten by homoplasy (McCracken and Sorenson, 2005). Thus, resolving these relationships might require considerably greater numbers of mitochondrial and fast-evolving nuclear characters.…”
Section: Mystacalismentioning
confidence: 99%